1984
DOI: 10.2113/gsecongeo.79.4.696
|View full text |Cite
|
Sign up to set email alerts
|

Paragenetic zoning and genesis of Cu-Zn-Fe-Pb-As sulfide skarn ores in a Proterozoic rift basin, Gruvaasen, western Bergslagen, Sweden

Abstract: The sulfide skarn ores of the Gruv•en mine area, western Bergslagen, Sweden, occur in a sequence of marbles and metatuffites intruded by basic sills and dikes. The mineralized area is exposed in a block-faulted and tilted structure within the Saxf• sedimentary rift basin. Sulfide mineralization occurs in zones within an area of intense potassic alteration. The central zone of the mineralized area is typified by Cu-W-Mo-bearing microcline skarns, Sn-bearing Cu-Zn-Fe sulfide skarns, a high Fe/Mg atomic ratio in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 15 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Hydrothermal alterations are a hallmark of the Bergslagen Group. Generally, seawater and hence a (shallow) marine environment is assumed as the source of the fluids (e.g., Baker & De Groot, 1983;Hellingwerf, 1984;Hellingwerf & Oen, 1986) which were responsible for widespread but strongly variable Mg-metasomatism and K/Na exchange in the Bergslagen Group. Terrestrial crater lakes exhibit an enormous variation in chemistries, some being just as magnesian as seawater (c. 1280 ppm; Varenkamp, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrothermal alterations are a hallmark of the Bergslagen Group. Generally, seawater and hence a (shallow) marine environment is assumed as the source of the fluids (e.g., Baker & De Groot, 1983;Hellingwerf, 1984;Hellingwerf & Oen, 1986) which were responsible for widespread but strongly variable Mg-metasomatism and K/Na exchange in the Bergslagen Group. Terrestrial crater lakes exhibit an enormous variation in chemistries, some being just as magnesian as seawater (c. 1280 ppm; Varenkamp, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although our emphasis herein is on the Grythyttan Slate Belt, we concur with Sundius' (1923) interpretation that the Grythyttan and the Saxån Slate Belts originally formed a single lithostratigraphic unit. Hellingwerf (1984Hellingwerf ( , 1986Hellingwerf ( , 1987 and Hellingwerf & Oen (1986) have shown that the SSB was affected by a synsedimentary hydrothermal system, fed by seawater, by analogy with widespread Na/K exchange reactions and Mg-metasomatism superimposed onto many of the volcanic rocks in western Bergslagen. The obvious consequence that most or all of the Grythyttan Slate Formation was deposited in a marine environment will be discussed later on.…”
Section: Grythyttan Slate Formationmentioning
confidence: 99%
“…H 2 or CH 4 etc. ; fugacity coefficients of H20 gas (Hellingwerf, 1984;Kalogeropulos, 1983), but recent fluid inclusion studies reveal that for 473 K and the CO2 isochore 0.925, the pressure should be about 1.5 kbar. Assuming the same isochore for 573 K, the pressure should not exceed 2.25 kbar and for 443 K about 1.2 kbar.…”
Section: (~ Copyright the Mineralogical Societymentioning
confidence: 99%